Efek Nefroptotektif Ekstak Etanol Bawang Putih (Allium sativum L.) Pada Tikus Yang Diinduksi Rifampicin - Fadira, Nurazra; Lubis , Asyrun Alkhairi; Yunus , Muhammad (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2025)
Background: Drug-induced nephrotoxicity, particularly caused by rifampicin—a first-line antituberculosis drug is a significant contributor to acute kidney dysfunction. The search for effective and safe nephroprotective agents to mitigate this side effect is crucial, and garlic (Allium sativum L.), with its potent antioxidant content, has emerged as a promising candidate. Objective: To evaluate the nephroprotective effect of ethanol extract of garlic (EEG) in male white rats (Rattus norvegicus) induced with rifampicin, based on serum creatinine levels, relative kidney weight, and histopathological findings. Methods: An in vivo experimental study was conducted on 25 rats randomly divided into five groups: (GI) normal control (distilled water); (GII) negative control (rifampicin 100 mg/kg BW, intraperitoneal); and three treatment groups (GIII, GIV, GV) receiving rifampicin 100 mg/kg BW and EEG at doses of 50, 120, and 300 mg/kg BW orally. Treatments were administered for 10 days. The measured parameters were serum creatinine levels, relative kidney weight, and histopathological damage scores (degeneration, necrosis, inflammatory cell infiltration). Results: Rifampicin induction (GII) significantly increased serum creatinine levels (1.28 ± 0.79 mg/dL) compared to the normal control (0.57 ± 0.05 mg/dL) (p<0.001). Administration of EEG at doses of 50, 120, and 300 mg/kg BW significantly reduced creatinine levels (0.53 ± 0.05; 0.51 ± 0.18; 0.51 ± 0.04 mg/dL, respectively). The relative kidney weight was highest in GII (1.6%), whereas treatment groups showed values close to normal. Histopathological analysis revealed the highest damage score in GII (score 2; 25–50%), while treatment groups, particularly the 300 mg/kg BW dose, showed the mildest damage (score 1; 5–25%). Conclusion: Ethanol extract of garlic exerts nephroprotective effects against rifampicin-induced kidney damage in rats, as evidenced by reduced serum creatinine levels, improvement in relative kidney weight, and amelioration of histopathological structures. These protective effects were dose-dependent, with the 300 mg/kg BW dose showing the most optimal outcome.